LEXICAL STYLISTIC DEVICES: METAPHOR, METONYMY, IRONY, AND EPITHET - Axmatxonova Mubina; Abdulazizova Sevara (TADQIQOTLAR, 2025)
This article explores four key lexical stylistic devices—metaphor, metonymy, irony,  and  epithet—which  are  essential  tools  for  enhancing  expressive  power  in English  language  and  literature.  Each  device  is  explained  with  definitions  and examples to help readers understand how they add emotional and imaginative depth to communication.